Variabilidad de la frecuencia cardiaca, cortisol salival y respuesta de ansiedad pre-entrenamiento y pre-competición: correlación test CSAI-2 (2017)
The integration of all the information and tools of measurement of anxiety and stress was used for the benefit of the athletes in order to use the results in favor of the training processes and competences, taking into account the need to improve the perception of Situations and their demands through faster processes of available information, and search for solutions on the appropriate behaviors referring to the actions and / or behaviors that an athlete develops in front of the stimuli that he receives and the bonds that he establishes with his environment, Thus achieving a prompt and vigorous response to the diversity of sensations. The objective of the present study was to investigate physiological and psychological states prior to pre-competition and pre-training included 24 male athletes from three different sports: canoeing athletes (CA), street runners (SR) and jiu jitsu (JJ). The Competitive State Anxiety Inventory-2 (CSAI-2), salivary cortisol and heart rate variability (HRV) were determined in two moments (pre-training and pre-competitive) to evaluate physiological and psychological parameters. A comparison of these situational behaviors on the athletes in the two moments.